HTERT promoter mutations in chondrosarcomas associate with progression and disease-related mortality. (December 2018) - Lin, Yingbo; Seger, Nelly; Chen, Yi; Hesla, Asle; Wejde, Johan; Ghaderi, Mehran; Tsagkozis, Panagiotis; Larsson, Olle; Haglund, Felix
Abstract Chondrosarcomas are malignant skeletal tumors with chondroid differentiation. Prognosis is largely dependent on histological grading, which suffer from significant interobserver variability. Telomerase activity and abundanttelomerase reverse transcriptase (hTERT ) expression has previously been associated with chondrosarcoma grade and metastasis. We therefore analyzed thehTERT promoter in clinicopathologically well-characterized chondrosarcomas (grade 1–3) from 87 patients. Using Sanger sequencing we identified an activating −124 C > T mutation in 23 cases (26%). Promoter mutations were significantly associated with increased histological grade (8% of grade 1, 32% of grade 2 and 46% of grade 3, P = 0.002), suggesting a role in tumor progression. In four chondrosarcomas where the histopathological grade was heterogenous, thehTERT mutation was only identified in the higher-grade areas. Additionally, hTERT promoter mutations were significantly associated with worse metastasis-free survival (P = 0.018), chondrosarcoma-specific survival (P = 0.022) and older patient age (P = 0.003). These data suggest thathTERT promoter mutations are common in high grade conventional chondrosarcomas. Granted that additional studies can confirm these findings;hTERT promoter analysis could potentially serve as an adjuvant prognostic marker in routine chondrosarcoma grading. This study reinforces the rationale of telomerase targeted therapy in a subset of chondrosarcomas.